The Effect of Using Wordwall-Based Interactive Learning Media in Increasing Students' Learning Motivation at SMP Negeri 4 Dompu - Khatimah, Husnul; Rizzaludin, Rizzaludin; Nurjannah, Nurjannah; Sumiyati, Sumiyati; Nurmi, Nurmi; Farhan, Danul; Amelia, Dinda (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This study aims to determine the effect of using interactive learning media based on wordwall in increasing the learning motivation of junior high school students. This type of research is a quasi-experimental (non-equivalent control group design) with a quantitative approach. The population is all 30 students in grade VII. The sample used is grade VII students consisting of two classes, namely class VII A as an experimental class consisting of 15 people and class VII B as a control class consisting of 15 people. The sampling technique uses saturated sampling. The data collection techniques consist of questionnaires, observation and documentation. As well as data analysis using prerequisite tests namely normality test, homogeneity test, and hypothesis test (t test). Data were obtained through pretest and posttest questionnaires. Based on the results of the study, it was obtained that student learning motivation in the experimental class after the use of wordwall media was 14 students or 94% who had very high motivation criteria and 1 student or 6% who had high motivation criteria. Meanwhile, in the control class that used picture media, there were 5 students or 33% who had very high motivation criteria and 10 students or 67% who had high motivation criteria. After that, the average value of the pretest questionnaire in the experimental class was 69.47 and the control class was 59.73. While the results of the posttest questionnaire showed an average of 89.73 for the experimental class and 80.40 for the control class. Based on the results of the posttest questionnaire in the experimental and control classes, it can be seen that the value of the experimental class questionnaire is greater than the value of the questionnaire in the control class, namely 89.73>80.40. So it can be concluded that the use of interactive learning media based on wordwall is more effective in increasing student learning motivation and can be shown from the results of the t-test which obtained a significance value of 0.000<0.05 which means Ha is accepted and Ho is rejected.